Abnormal Axial Diffusivity in the Deep Gray Nuclei and Dorsal Brain Stem in Infantile Spasm Treated with Vigabatrin - Simao, G.N. (AJNR Am J Neuroradiol, 2011)
We evaluated the DTI changes in the deep gray nuclei and dorsal brain stem, which demonstrated abnormal T2 and/or diffusion signal intensity, in 6 patients with infantile spasm treated with vigabatrin compared with 6 age-matched controls. Regions of interest were placed in the globi pallidi, thalami, and dorsal brain stem; FA, trace, D(‖), and D(⊥) were measured. Patients on vigabatrin had significantly lower FA in both globi pallidi (P = .01) and the dorsal brain stem (P < .01), significantly lower trace in both globi pallidi (P = .01) and the thalami (P = .02 and .01 for right and left, respectively), and significantly lower D(‖) in both globi pallidi (P ≤ .01), the thalami (P < .01), and the dorsal brain stem (P = .03). There were no significant differences in D(⊥) of the globi pallidi, thalami, or dorsal brain stem in patients compared with controls. The findings suggest that axonal changes play a greater role in the observed abnormal signal intensity, with lesser contribution from myelin changes.